Bendamustine, thalidomide and dexamethasone combination therapy for relapsed/refractory myeloma patients: results of the MUKone randomized dose selection trial. (20th April 2015) - Schey, Steve; Brown, Sarah R.; Tillotson, Avie‐Lee; Yong, Kwee; Williams, Cathy; Davies, Faith; Morgan, Gareth; Cavenagh, Jamie; Cook, Gordon; Cook, Mark; Orti, Guillermo; Morris, Curly; et al.
Summary There is a significant unmet need in effective therapy for relapsed myeloma patients once they become refractory to bortezomib and lenalidomide. While data from the front line setting suggest bendamustine is superior to melphalan, there is no information defining optimal bendamustine dose in multiply‐treated patients. We report a multi‐centre randomized two‐stage phase 2 trial simultaneously assessing deliverability and activity of two doses of bendamustine (60 mg/m2 vs. 100 mg/m2) days 1 and 8, thalidomide (100 mg) days 1–21 and low dose dexamethasone (20 mg) days 1, 8, 15 and 22 of a 28‐d cycle. Ninety‐four relapsing patients were treated on trial, with a median three prior treatment lines. A pre‐planned interim deliverability and activity assessment led to closure of the 100 mg/m2 arm due to excess cytopenias, and led to amendment of entry criteria for cytopenias. Non‐haematological toxicities including thromboembolism and neurotoxicity were infrequent. In the 60 mg/m2 arm, treatment was deliverable in 61·1% subjects and the partial response rate was 46·3% in the study eligible population, with 7·5 months progression‐free survival. This study demonstrates bendamustine at 60 mg/m2 twice per month with thalidomide and dexamethasone is deliverable for repeated cycles in heavily pre‐treated myeloma patients and has substantial clinical activity.